Enthesis tissue engineering: biological requirements meet at the interface - Calejo, I. (2019)
Tendon-to-bone interface (enthesis) exhibits a complex multiscale architectural and compositional organization maintained by a heterogeneous cellular environment. Orthopedic surgeons have been facing several challenges when treating tendon pullout or tear from the bony insertion due to unsatisfactory surgical outcomes and high retear rates. The limited understanding of enthesis hinders the development of new treatment options toward enhancing regeneration. Mimicking the natural tissue structure and composition is still a major challenge to be overcome. In this review, we critically assess current tendon-to-bone interface tissue engineering strategies through the use of biological, biochemical, or biophysical cues, which must be ultimately combined into sophisticated gradient systems. Cellular strategies are described, focusing on cell sources and cocultures to emulate a physiological heterotypic niche, as well as hypoxic environments, alongside with growth factor delivery and the use of platelet-rich hemoderivatives. Biomaterial design considerations are revisited, highlighting recent progresses in tendon-to-bone scaffolds. Mechanical loading is addressed to uncover prospective engineering advances. Finally, research challenges and translational aspects are considered. In summary, we highlight the importance of deeply investigating enthesis biology toward establishing foundational expertise and integrate cues from the native niche into novel biomaterial engineering, aiming at moving today's research advances into tomorrow's regenerative therapies.